Britannica guide to political and social movements that changed the modern world / edited by Heather M.Campbell - "Campbell,Heather M.(ed.)" (New York, 2010)
Few forces are more powerful than a group of people united by a common cause. Collective objectives, known as movements, have been known to radically alter the course of human history. This book traces an array of important political and social movements from their inception to their apex, with plentiful side discussions of notable proponents.
Keywords: "History,Modern"